Growth and yield responses of upland NERICAs to variable water management under field conditions. (2nd January 2017) - Kikuta, Mayumi; Makihara, Daigo; Arita, Naoya; Miyazaki, Akira; Yamamoto, Yoshinori
Abstract: This study aimed to investigate the possible causes for inconsistent performances of upland New Rice for Africa (NERICA) varieties in uplands and lowlands, while identifying important determinants in grain yield under deficient soil moisture. We compared the growth and yield of NERICA 1 and NERICA 5 to those of Yumenohatamochi, a Japanese upland variety, and Hinohikari, a Japanese lowland variety, subjected to different water management regimes (continually flooded, supplementary irrigation, and non-irrigation). Under conditions of deficient soil moisture, panicle number per square meter, spikelet number per panicle, and 1000-grain weight of NERICAs decreased, whereas the panicle number of the Japanese varieties experienced little change. In contrast, the grain filling ratio was unaffected by water management, irrespective of variety. The primary source of yield reduction under low soil water conditions was a decrease in spikelet number per panicle, and water stress intensity was the primary factor for the degree of this reduction. Variation in the abortion of secondary rachis-branches caused differences between NERICAs in their spikelet number response to soil moisture deficiency. The inconsistency in NERICA performance across uplands vs. lowlands can be partially attributed to variation in yield response to low soil water conditions. Moreover, water stress intensity and the presence of a water gradient along the vertical soil profile may combine to affect the fluctuation in NERICA performance under upland conditions.